2017
DOI: 10.5430/jha.v6n3p15
|View full text |Cite
|
Sign up to set email alerts
|

Optimal governance of patient safety: A qualitative study on barriers to and facilitators for effective internal audit

Abstract: Objective: While internal audits are widely used, insight into the essential components of the internal audit to govern patient safety is limited. The aim of this study is to explore factors that hinder and stimulate internal audits as an effective patient safety governance tool for hospital boards. Methods: A qualitative interview study in six Dutch hospitals. Interviews (n = 43) were held with auditees, quality officers, boards of directors and boards of supervisors. Data were collected and analysed using Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 25 publications
(37 reference statements)
3
29
0
Order By: Relevance
“…Somehow there many reasons that could in uence P&Fs preference and willingness to engage in their healthcare. Some studies revealed that there is a general expectation that healthcare professionals, "know what they are supposed to be doing" and a common assumption that they always did what they were supposed to do, specially the most basic duties as washing their hands properly or administering the correct medications 15,[27][28][29] . Also, some studies suggest that checking to ensure that healthcare professionals were doing their job correctly could be embarrassing and damage relationship with them 20,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somehow there many reasons that could in uence P&Fs preference and willingness to engage in their healthcare. Some studies revealed that there is a general expectation that healthcare professionals, "know what they are supposed to be doing" and a common assumption that they always did what they were supposed to do, specially the most basic duties as washing their hands properly or administering the correct medications 15,[27][28][29] . Also, some studies suggest that checking to ensure that healthcare professionals were doing their job correctly could be embarrassing and damage relationship with them 20,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is well established that patients and their families (including friends and informal caregivers) have unique knowledge and are able to detect if their care is safe and patient-centred. 6,[15][16] Patients and their families are present during the whole care episode and often are the only members who are aware of lapses in safety thus being a useful source of information about patient safety. Information gathered by patients and their families (P&Fs) gives healthcare organizations an opportunity to learn and improve the system of care.…”
Section: Introductionmentioning
confidence: 99%
“…At each hospital, different stakeholders were asked to fill in a questionnaire. Stakeholders involved in governance and the auditing process were selected based on a qualitative study [ 13 ] in which a stakeholder analysis [ 20 23 ] was performed. The following six stakeholders per hospital received the questionnaire: (1) a member of the board of directors, (2) the chief of medical staff, (3) the nursing officer, (4) the head of the department of orthopaedic surgery, (5) the head of the internal medicine department and (6) the director of the quality and patient safety department (or unit).…”
Section: Methodsmentioning
confidence: 99%
“…Auditing is a multiple-source method that evaluates whether standards and regulations are being followed [ 10 ]. In contrast to clinical auditing, which focusses on one specific clinical area and is initiated by healthcare professionals [ 11 , 12 ], the audit to which we refer in this study is a hospital-wide audit, which focusses on auditing all departments on a periodic basis and is initiated by hospital boards [ 13 ], as is shown in Fig. 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation